Psychological flexibility: A psychological mechanism that contributes to persistent symptoms following mild traumatic brain injury?. (October 2020) - Faulkner, Josh W.; Theadom, Alice; Mahon, Susan; Snell, Deborah L.; Barker-Collo, Suzanne; Cunningham, Kay
Abstract: Persistent symptoms following a mild traumatic brain injury (mTBI) can have profound implications on all aspects of an individual's functioning. Psychological factors have a significant role in contributing to the development of persistent post-concussion symptoms and predicting outcomes. Biopsychosocial explanations have therefore been applied to prognostic models of mTBI. What is not evident in the literature to date is an understanding of the psychological mechanisms that may be important in mediating the various psychological factors in these models. The construct of psychological flexibility holds promise in this regard. Psychological flexibility is the ability to act in alignment with values in the presence of inner discomfort such as pain and distress. It is hypothesised that psychological flexibility has a significant role in the development and maintenance of persistent symptoms following mild traumatic brain injury. The rationale that forms the basis of this hypothesis is as follows: a relationship exists between psychological flexibility and pre-injury psychological risk factors; psychological flexibility is vulnerable to the pathophysiology associated with mTBI; post-injury psychological and neuropsychological factors exacerbate and maintain psychological inflexibility; and psychological flexibility underlies psychological responses to mTBI that contribute to unfavourable outcomes. A discussion of the literature that pertains to each of these points is presented. Based on this hypothesis, we conclude, that there is rationale to empirically explore the role of psychological flexibility in mTBI and its relationship to outcomes. This may also lead to evaluation of specific interventions that target this psychological mechanism in mTBI, such as Acceptance and Commitment Therapy, and improve outcomes for this population.